ALK Inhibitors in the Treatment of ALK Positive NSCLC - Khan, Muhammad; Lin, Jie; Liao, Guixiang; Tian, Yunhong; Liang, Yingying; Li, Rong; Liu, Mengzhong; Yuan, Yawei (Frontiers in Oncology, 2019)
Background: ALK inhibitors have shown positive advance in the treatment of ALK+ NSCLC. They have achieved better results in prolonging the progression free survival and improving quality of life in comparison to chemotherapy. We have assembled the evidence related to the efficacy and safety of these agents in the treatment of ALK positive NSCLC. Methods & Materials: A comprehensive search was conducted using electronic databases of PubMed, Medline and Cochrane Library to identify the studies involving comparison of ALK inhibitors to chemotherapy and Next generation ALK inhibitors to crizotinib. PFS was the primary outcome while other outcomes like ORR, adverse events, quality of life and OS were also analyzed and compared. Hazard ratios and odds ratios obtained were analyzed using fixed effect or random effects model in Review Manager Software. Results: A total of 11 studies (n=3022) met the criteria for inclusion in this review and meta-analysis. ALK inhibitors including crizotinib, ceritinib and alectinib revealed significantly better PFS (HR 0.42 [0.35, 0.50; p<0.00001]), ORR (Overall OR 6.59 [4.86, 8.94; p<0.00001] as compared to chemotherapy in the first line as well as second line treatment settings. Intracranial response rate was better with ALK inhibitors (ceritinib and alectinib) as compared to chemotherapy (OR 6.51 [2.86, 14.83; p<0.00001]. No significant increase in grade 3 or 4 adverse events was observed with crizotinib (OR 1.21 [0.82, 1.77; p=0.34]) or ceritinib (OR 1.49 [0.86, 2.57; p=0.17]) when compared to chemotherapy individually. Quality of life indicators assessed were significantly improved with ALK inhibitors. Next generation agents (ceritinib and alectinib) revealed significant improvement in PFS (HR 0.50 [0.43, 0.58; p<0.00001]), ORR (OR 1.56 [1.15, 2.11; p=0.004] in comparison to crizotinib. Alectinib yielded better response intra-cranially than crizotinib. Alectinib by far resulted in fewer adverse events than chemotherapy or crizotinib. Conclusions: Overall ALK inhibitors are safe and effective treatment option in ALK+ non-small cell lung cancer. Of the ALK inhibitors, Alectinib is safer and more effective intra-cranially and can be preferred as first option.